CONSUMER BEHAVIOUR TOWARDS ONLINE SHOPPING IN TAMILNADU (International Journal of Food and Nutritional Sciences, 2022)
Consumer behaviour is the study of how individuals, groups, and organisations choose, purchase, utilise, and dispose of ideas, products, and services to meet their needs and desires. It refers to the behaviours of customers in the marketplace as well as the motivations behind such actions. Marketers hope to be able to identify which items are required in the marketplace, which are outdated, and how best to display the commodities to customers by knowing what motivates people to purchase certain goods and services. “It is the customer who decides what business is,” wrote Peter F. Drucker 1 (1988). What a customer believes he is purchasing, what he deems "value," is crucial - it defines what a company is, what it produces, and if it will succeed." Consumer behaviour is described by Schiffmanand Kanuk2 (1978) as "the behaviour that consumers exhibit in looking for, buying, consuming, and evaluating goods, services, and ideas that they believe will meet their requirements." “Consumer behaviour is the process and actions individuals participate in while looking for, choosing, buying, using, evaluating, and disposing of goods and services to fulfil their wants and desires,” according to Belch and Belch3 (1985).”.